The use of the race/color variable in public health: possibilities and limitations - Edna Maria de Araújo; Maria da Conceição N. Costa; Vijaya K. Hogan; Tânia Maria de Araújo; Acácia Batista; Lúcio O. A. Oliveira (Faculdade de Medicina de Botucatu (Unesp), 2010)
This study aimed to discuss the use of the race/color variable as a determining factor of social difference and social exposure to the risk of illness and death. It is a reflection on the present production of the national and international literature in the Public Health and Epidemiology field on this subject. The study examined 47 original and review papers in the period 1990 to 2005. It was observed that international studies have aimed to debate and ground the use of the race/color variable in the health field. In Brazil, the use of this variable in studies about health inequalities is still incipient, but within the few investigations performed, differentials have been evidenced, which instigates the production of further research in this direction. The study of the role of race/color in the production of health differentials could contribute to make policies focusing on reducing health inequalities.